Reports of two peculiar pigmented new species of genus Homidia (Collembola: Entomobyridae) from Southern China, with description of subadults chaetotaxy - Pan, Zhi-Xiang; Yang, Wan-Qin (Zootaxa, 2019)
Two new species with peculiar pigmentation of the genus Homidia from Guangdong Province, Southern China are described here, Homidia chroma sp. nov. and Homidia leniseta sp. nov. H. chroma is characterized by chrome pigmentation on lateral side of terga, two macrochaetae on medial abdominal segment (Abd.) III and six macrochaetae on postero-medial Abd. IV, up to 68 sensory chaetae present on Abd. IV, and five apical smooth chaetae on posterior face of ventral tube. H. leniseta is easily identified by unique colour pattern, smooth labial chaetae l2, G1–4 and H1–3, and short trichobothria on Abd. II–IV. Illustrations of adults of this two new species, chaetotaxy of the first instar larvae of H. chroma and subadults of H. leniseta are provided herein.